11x-12=4x-1

Simple and best practice solution for 11x-12=4x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-12=4x-1 equation:


Simplifying
11x + -12 = 4x + -1

Reorder the terms:
-12 + 11x = 4x + -1

Reorder the terms:
-12 + 11x = -1 + 4x

Solving
-12 + 11x = -1 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-12 + 11x + -4x = -1 + 4x + -4x

Combine like terms: 11x + -4x = 7x
-12 + 7x = -1 + 4x + -4x

Combine like terms: 4x + -4x = 0
-12 + 7x = -1 + 0
-12 + 7x = -1

Add '12' to each side of the equation.
-12 + 12 + 7x = -1 + 12

Combine like terms: -12 + 12 = 0
0 + 7x = -1 + 12
7x = -1 + 12

Combine like terms: -1 + 12 = 11
7x = 11

Divide each side by '7'.
x = 1.571428571

Simplifying
x = 1.571428571

See similar equations:

| -2x+26=6 | | 51*3.28= | | x+30x=180 | | 4x+6x-(6x+5)= | | 3sinx+5cox+5=0 | | 6.144*2.20= | | f(2.885)=-5.89x+6.357 | | 3x+18=10x+4 | | -27.018=31.572x-17.741 | | 0=2+.6x | | y=x+262.83 | | 5x^2-305=15 | | 3(4x-5)=10(x+4) | | 2(1-y)=2y-6 | | 27+3x=37 | | xsqrt(12)+9=xsqrt(3) | | 5x-3=14x-50 | | 5x-3=12x-50 | | 12-12x=18-10x | | -1+4k=-17 | | 2y^3-3y^2=12-8y | | k+466-28= 4 | | 5ax+2c=-13c | | 3.4=1.5-0.5y | | -4+2s=6 | | 12x+8=8x-(-20) | | (5x+17)(8x-4)= | | x+y=800 | | -10x+2y=2 | | 6x=-60+4x | | 4x+2+3x-1+x=81 | | -3(-7h-9k+8)= |

Equations solver categories